2004
DOI: 10.1021/ja049734s
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Catalysis with CO2:  Direct Synthesis of Optically Active Propylene Carbonate from Racemic Epoxides

Abstract: This communication describes a convenient route to optically active propylene carbonate by a catalytic kinetic resolution process resulting from the coupling reaction of CO2 and racemic epoxides using simple chiral SalenCo(III)/quaternary ammonium halide catalyst systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
165
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 346 publications
(173 citation statements)
references
References 29 publications
(19 reference statements)
7
165
0
1
Order By: Relevance
“…under extremely mild and solvent-free conditions. 99 Unfortunately the kinetic resolution coefficients measured (k rel < 10) were still far from being optimal compared with wellknown hydrolytic kinetic resolution methods. 100 More recently, the same group reported a multichiral Co(III) complexes 22 ( Figure 9) which was used in conjuction with the 2,4-dinitrophenolate salt of PPN (PPN-DNP) as the nucleophilic co-catalyst.…”
Section: Methodsmentioning
confidence: 99%
“…under extremely mild and solvent-free conditions. 99 Unfortunately the kinetic resolution coefficients measured (k rel < 10) were still far from being optimal compared with wellknown hydrolytic kinetic resolution methods. 100 More recently, the same group reported a multichiral Co(III) complexes 22 ( Figure 9) which was used in conjuction with the 2,4-dinitrophenolate salt of PPN (PPN-DNP) as the nucleophilic co-catalyst.…”
Section: Methodsmentioning
confidence: 99%
“…Notably, the chiral Lewis base did not contribute significantly to the enantioselectivity. Later, Lu reported the use of a similar cobalt(III)salen complex 4 in the presence of two equivalents of n-NBu 4 Cl (n-tetrabutylammonium chloride) for the synthesis of enantioenriched propylene carbonate 2a [11]. The bulky p-toluene-sulfonate counterion was essential to obtain high enantioselectivity.…”
Section: Cobalt(iii) Salen Complexesmentioning
confidence: 99%
“…Although a number of metal-based salen complexes have been developed [11,18] only a few catalytic systems gave comparable results to that of cobalt-based complexes. Recently, North et al have reported the use of aluminium(III) and chromium(III) salen complexes for the kinetic resolution of terminal epoxides via carbon dioxide coupling (Figure 4) [27].…”
Section: Other Metal Salen Complexesmentioning
confidence: 99%
“…Lu and co-workers [26] first described the preparation of optically pure cyclic carbonates from racemic epoxides by a catalytic kinetic resolution process involving several chiral (salen)CoX complexes and quaternary ammonium halides. And the reaction of racemic propylene oxide with 0.55-0.60 equiv of CO 2 was catalyzed by 0.1 mol % of (salen)Co III (O 2 CCCl 3 ) complex 2b and 0.1 mol % of n-Bu 4 NBr under solvent-free conditions.…”
Section: (Salen)cr For the Coupling Of Co 2 And Epoxidesmentioning
confidence: 99%